ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN PADA TOKO SARI BUSANA DENGAN MENGGUNAKAN METODE PROTOTYPE - Lestari, Ni Putu Yowi; Putri, I Gusti Agung Pramesti Dwi; Kusuma, Ni Putu Noviyanti (Politeknik Bisnis Indonesia, 2024)
Sari Busana is a fashion destination that sells a wide selection of clothing ranging from kebaya, school clothes and others. An accounting information system is a system that processes data and transactions to produce useful information. Currently, the Sari Busana still has not implemented an accounting information system in the sales recording process and still uses manual recording which has an impact on performance not being integrated and the level of data validity not running as expected. The aim of this research is to design a computerized sales accounting information system. The research method used is the Prototype method. The results of this research are a sales system design that can be accessed by the cashier, warehouse department and owner in accordance with user needs. The results of the system design demo given to the user stated that the system that had been designed was in accordance with the user's needs.